Targeted and Salvage Therapies Benefit Patients With Thyroid Cancer - Boltz, Kathy (MD Conference Express, 2015)
Sorafenib and lenvatinib can be effective for advanced differentiated thyroid cancer, and vandetanib and cabozantinib can be effective options for advanced medullary thyroid cancer. When first-line tyrosine kinase inhibitors fail for patients, evidence supports salvage therapy for differentiated thyroid cancer but is less compelling for medullary thyroid cancer.